Visible light-induced α-C(sp3)-H acetalization of saturated heterocycles catalyzed by a dimeric gold complex - Si, Xiaojia; Zhang, Lumin; Wu, Zuozuo; Rudolph, Matthias; Asiri, Abdullah M.; Hashmi, A. Stephen K. (Organic letters, 2020)
Saturated heterocyclic acetals are useful fragments in organic synthesis and other fields. Herein, C(sp3)-H dehydrogenative cross-couplings of ethers, tetrahydrothiophenes, and pyrrolidines were achieved under visible light irradiation by using iodobenzene and an in situ-formed gold complex. The broad functional group compatibility and substrate scope indicate that our strategy is a promising way to synthesize acetal analogues. The method was successfully applied in late-stage modifications of bioactive molecules. Gram scale syntheses and mechanistic studies are also presented.
Gesehen am 16.09.2020